THE EFFECT OF INDONESIA’S LEADING COMMODITIES IN THE MINING SECTOR ON THE INDONESIA COMPOSITE INDEX (ICI) - Hana, Wardah Nurnabilah; Sebayang, Karuniana Dianta Arfindo; Iranto, Dicky (Jurnal Pendidikan Ekonomi, Perkantoran, dan Akuntansi, 2025)
This study aims to determine the effect of Indonesia's leading natural resources, especially in the mining sector, on the Indonesian economy as reflected in the Indonesia Composite Index (ICI). This study uses a quantitative approach, using monthly time series data for 9 years from 2016 to 2024. The testing was conducted using multiple regression analysis with data analysis tools using Eviews 12 software. Data analysis involved two main steps: 1) testing classical assumptions such as normality, multicollinearity, autocorrelation, and heteroscedasticity; 2) multiple linear regression analysis; and 3) hypothesis testing such as partial or t-tests, simultaneous or F-tests, and the coefficient of determination (R²). The results of the study indicate that coal and gold prices have a significant positive effect on the Indonesia Composite Index (ICI). Nickel prices have no effect on the ICI. Simultaneously, the three commodity variables have a significant influence on the IHSG with a coefficient of determination of 59.54%. This finding indicates that Indonesia's leading commodities, namely coal, nickel, and gold, play an important role in influencing the capital market.